MANAJEMEN PEMBELAJARAN BAHASA INGGRIS PADA PROGRAM PENDIDIKAN KESETARAAN PAKET C - Yesino, Leonardus; Apiyanti, Pina Dewi; Budiman, Dadan; Zuhri, Saepudin; Yoseptry, Ricky; Iriantara, Yosal (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This study analyzes the management of English language learning in the Equal Education Program Package C at PKBM Insan Muwahid Garut. Using a qualitative approach and case study method, data were collected through interviews, observations, and documentation. The results indicate that the management of learning includes planning based on a flexible curriculum, implementation using interactive and contextual methods, and formative and summative evaluations. The learning is designed to enhance the communication skills of the participants. This study recommends the development of more effective learning management to support English language learning in the equal education program.